Kommentierte Artenliste der Spinnen Bayerns (Araneae) - Blick, Theo (Arachnologische Mitteilungen, 1991)

(untitled)
The checklist contains informations on records after 1970 in seven bavarian counties ("Bezirke") an in whole Bavaria before 1970. A total of 747 species is known from Bavaria. 14 species (Dysdera ninnii, Gonatium ensipotens, Hilaira montigena, Janetschekia monodon, Lessertinella kulczynskii, Peponocranium praeceps, Scotinotylus antennatus, Trichoncus simoni, Bathyphantes setiger, Lepthyphantes jacksonoides, Lepthyphantes variabilis, Maro lehtineni, Tricca alpigena, Gnaphosa rhenana) are mentioned here for the first time in Germany, 11 are new for southern Germany and 43 new for Bavaria.